Penerapan Fuzzy Logic pada Sistem Controlling Suhu dan Kelembapan Solar Dryer Berbasis Internet of Things - Kristian Juri Damai Lase; Antonius Bima Murti Wijaya; Gogor Christmas Setyawan (Progresif: Jurnal Ilmiah Komputer, 2025)
The utilization of solar dryer technology as a renewable energy-based drying solution still faces challenges, particularly in monitoring and controlling temperature and humidity in remote areas with unstable internet connectivity. This research aims to design and develop a temperature and humidity control system for solar dryers based on the Internet of Things (IoT), implementing fuzzy logic as an adaptive decision-making method. The system employs Arduino Uno, DHT22 sensor, SIM800L, Raspberry Pi, and a GSM modem. Temperature and humidity data are transmitted via SMS to the Raspberry Pi as a gateway, then forwarded to a cloud server and processed using fuzzy logic to automatically control the fan when thresholds are exceeded. The test results show that the system operates in real-time, is responsive and accurate, and reliably performs fuzzy logic-based automatic control even in areas with limited internet access. This system proves effective as a solution for remote IoT-based temperature and humidity monitoring and control.Keywords: Solar Dryer; Fuzzy Logic; Raspberry Pi; Arduino; Internet of Things. AbstrakPemanfaatan teknologi solar dryer sebagai solusi pengeringan energi terbarukan masih menghadapi kendala, khususnya dalam aspek pemantauan dan pengendalian suhu serta kelembapan di lokasi terpencil yang tidak terjangkau jaringan internet stabil. Penelitian ini bertujuan untuk merancang dan mengembangkan sistem pengendali suhu dan kelembapan solar dryer berbasis Internet of Things (IoT) dengan menerapkan logika fuzzy sebagai metode pengambilan keputusan adaptif. Sistem ini menggunakan perangkat Arduino Uno, sensor DHT22, SIM800L, Raspberry Pi, dan modem GSM. Data suhu dan kelembapan dikirim melalui SMS ke Raspberry Pi sebagai gateway, lalu diteruskan ke server cloud dan diproses oleh logika fuzzy untuk mengendalikan kipas secara otomatis jika ambang batas terlampaui. Hasil pengujian menunjukkan bahwa sistem bekerja secara real-time, responsif, dan akurat, serta mampu menjalankan kontrol otomatis berbasis fuzzy logic secara andal meskipun berada di lokasi minim internet. Sistem ini terbukti efektif sebagai solusi monitoring dan kontrol suhu kelembapan jarak jauh berbasis IoT.Kata Kunci: Solar Dryer; Fuzzy Logic; Raspberry Pi; Arduino; Internet of Things.